Zirconium Alloys Produced by Recycling Zircaloy Tunings - Gamba, Nadia Soledad (2013)
Zircaloy chips were recycled to successfully produce Zr–Ti alloys with bcc structure and different compositions. The procedure developed involves two steps. First, the reactive mechanical alloying (RMA) of the zircaloy tunings and Ti powders was performed to produce metal hydride powders, with a high refinement of the microstructure and a Zr–Ti homogeneous composition. Second, the metal hydride powders were thermally decomposed by heating up to 900 C to synthesize the Zr-based alloy with a selected composition. The change in the nature of the powders from ductile to brittle during milling avoids both cold working phenomena between the metals and the use of a control agent. A minimum milling time is necessary to produce the solid solution with the selected composition. The microstructure and structure of the final alloys obtained was studied. The present procedure could be extended to the production of Zrbased alloys with the addition of other metals different from Ti.